Computing in Civil Engineering 2019 : Smart Cities, Sustainability, and Resilience. - Cho, Yong K. (American Society of Civil Engineers, 2019)
This collection contains 73 peer-reviewed papers on smart cities, sustainability, and resilience presented at the ASCE International Conference on Computing in Civil Engineering 2019, held in Atlanta, Georgia, June 17-19, 2019.
Keywords: Computer-aided engineering -- Congresses.; Civil engineering -- Data processing -- Congresses.; Smart cities -- Congresses.; elektronické knihy; electronic books